Development of a Novel NGS Methodology for Ultrasensitive Circulating Tumor DNA Detection as a Tool for Early-Stage Breast Cancer Diagnosis - Jiménez-Rodríguez, Begoña; Alba-Bernal, Alfonso; López-López, Esperanza; Quirós-Ortega, María Elena; Carbajosa, Guillermo; Garrido-Aranda, Alicia; Álvarez-Pérez, Martína; Godoy-Ortiz, Ana; Queipo-Ortuño, María Isabel; Vicioso-Recio, Luis Prudencio; Díaz-Córdoba, Gema; Roldán-Díaz, María Dunia; et al. (IOAP-MDPI, 2022)
Breast cancer (BC) is the most prevalent cancer in women. While usually detected when localized, invasive procedures are still required for diagnosis. Herein, we developed a novel ultrasensitive pipeline to detect circulating tumor DNA (ctDNA) in a series of 75 plasma samples from localized BC patients prior to any medical intervention. We first performed a tumor-informed analysis to correlate the mutations found in tumor tissue and plasma. Disregarding the tumor data next, we developed an approach to detect tumor mutations in plasma. We observed a mutation concordance between the tumor and plasma of 29.50% with a sensitivity down to 0.03% in mutant variant allele frequency (VAF). We detected mutations in 33.78% of the samples, identifying eight patients with plasma-only mutations. Altogether, we determined a specificity of 86.36% and a positive predictive value of 88.46% for BC detection. We demonstrated an association between higher ctDNA median VAF and higher tumor grade, multiple plasma mutations with a likelihood of relapse and more frequent TP53 plasma mutations in hormone receptor-negative tumors. Overall, we have developed a unique ultra-sensitive sequencing workflow with a technology not previously employed in early BC, paving the way for its application in BC screening.
Keywords: Cancer; Circulating tumor DNA; Ultra-deep sequencing; Early breast cancer; Liquid biopsy